2011
DOI: 10.7773/cm.v38i1b.1808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic exudates of Phaeodactylum tricornutum on the Fe(II) oxidation rate constant

Abstract: ABSTRACT. Fe(II) oxidation kinetics were studied in seawater and in seawater enriched with exudates excreted by Phaeodactylum tricornutum as an organic ligand model. The exudates produced after 2, 4, and 8 days of culture at 6.21 10 7 , 2.29 10 8 , and 4.98 10 8 cell L -1 were selected. The effects of pH (7.2-8.2), temperature (5-35 ºC), and salinity (10-36.72) on the Fe(II) oxidation rate were studied. All the data were compared with the results for seawater without exudates (control). The Fe(II) rate constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
1
14
0
1
Order By: Relevance
“…To this effect, the diatom was harvested in seawater with f/2 nutrients (control seawater) as the reference growth (Fig. 1) in close concordance with recent studies (Vasconcelos and Leal 2008;Gonzá lez et al 2012). At these conditions, the cell density increased from 2 3 10 7 cells L 21 to 5.9 3 10 8 cells L 21 after 8 d of culture.…”
Section: Resultssupporting
confidence: 72%
“…To this effect, the diatom was harvested in seawater with f/2 nutrients (control seawater) as the reference growth (Fig. 1) in close concordance with recent studies (Vasconcelos and Leal 2008;Gonzá lez et al 2012). At these conditions, the cell density increased from 2 3 10 7 cells L 21 to 5.9 3 10 8 cells L 21 after 8 d of culture.…”
Section: Resultssupporting
confidence: 72%
“…The capacity of organic ligands to form a complex with Fe(III) and to reduce Fe(III) to the bioavailable Fe(II) species in seawater has been studied (van den Berg 1995; Santana-Casiano et al 2000;Rose and Waite 2003). The role of several polyphenols is related to the availability of Fe(II) in solution and the presence of natural exudates also retards the oxidation of Fe(II) (González et al 2012). Santana-Casiano et al (2014) reported that the phenolic compounds exuded from microalgae, such as sinapic acid and (+) catechin, have an influence in iron redox chemistry by favouring the persistence of Fe(II) for their requirements.…”
Section: Discussionmentioning
confidence: 98%
“…Complex redox cycling, such as the oxidation of reduced Fe(II) as it diffuses upwards, and the reduction of sinking Fe(III)(hydr)oxides occur near the redoxcline (Spencer and Brewer, 1971;Sorokin, 2002b;Yemenicioglu et al, 2006;Dellwig et al, 2010). [L t ] near the redoxcline will have consequences for the redox processes of Fe, since organic ligands are known to influence the oxidation and reduction of Fe (Santana-Casiano et al, 2000;Rijkenberg et al, 2006a;González et al, 2012) (in fact, this effect is used by CLE-aCSV, which change the half-wave potential of metals like Fe by complexing it to for example TAC). Increasing and decreasing oxidation rates of Fe(II) in seawater depend on the nature of the organic matter added (Santana-Casiano et al, 2000Rijkenberg et al, 2006a;González et al, 2012).…”
Section: Sources and Sinks Of Fe And Fe-binding Dissolved Organic Ligmentioning
confidence: 99%